2012
DOI: 10.1177/0363546512457552
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Meniscal Tears Associated With Tibial Plateau Fractures

Abstract: Meniscal repair of tears associated with tibial plateau fractures has good results. All patients had good or excellent clinical results. Second-look arthroscopy confirmed complete healing in 92% of meniscal tears when performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
(66 reference statements)
0
39
0
Order By: Relevance
“…Most studies have evaluated the success of managing a tibial plateau fracture by looking at radiographic and functional results [ 26 ]. The second-look arthroscopic evaluation not only provides a safe, quick, and accurate method of assessing outcomes, but it also provides the only way to show the healing of articular cartilage after a tibial plateau fracture has been treated [ 27 29 ]. So far, only three studies have used second-look arthroscopy to directly observe and assess the intra-articular structures after a tibial plateau fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have evaluated the success of managing a tibial plateau fracture by looking at radiographic and functional results [ 26 ]. The second-look arthroscopic evaluation not only provides a safe, quick, and accurate method of assessing outcomes, but it also provides the only way to show the healing of articular cartilage after a tibial plateau fracture has been treated [ 27 29 ]. So far, only three studies have used second-look arthroscopy to directly observe and assess the intra-articular structures after a tibial plateau fracture.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the actual condition of the articular cartilage varied significantly, even in patients with a normal joint range of motion and good clinical and radiological results. Ruiz-Ibán et al [ 29 ] studied 13 patients who had undergone combined arthroscopic treatment for a tibial plateau fracture and a meniscal tear. One patient had a grade II lesion with a clear decrease in his activity level and a low adjusted IKDC (International Knee Documentation Committee) score attributable to a chondral lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently emerged as a treatment option for tibial plateau fractures (Schatzker I-III), this method seems to be adopted by more and more surgeons in the world, as it benefits from the advantages of minimally invasive surgery - reduced hospitalization, faster recovery of knee mobility, reduced cutaneous complications [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other lesions (external meniscus is damaged in about 30–50% of cases, lesions of cartilage or osteochondral lesions) can simultaneously benefit from specific treatment, improving patient recovery. Tears of the anterior cruciate ligament are also frequent, most of the time partial [ 2 , 4 , 5 , 6 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Functional results are rated as excellent or good in 90% of patients with a low rate of severe complications, despite one post-operative compartment syndrome being reported. 24 Using our preferred technique (percutaneous, arthroscopically-assisted or open technique) we must ensure the goal of the surgery: to obtain anatomical reduction and a fracture fixation stable enough to allow early/immediate knee motion.…”
Section: What Are the Indications For Surgical Treatment?mentioning
confidence: 99%